Quantifying the relative molecular orbital alignment for molecular junctions with similar chemical linkage to electrodes - Bâldea, Ioan (Nanotechnology, 2014)
Estimating the relative alignment between the frontier molecular orbitals (MOs) that dominates the charge transport through single-molecule junctions represents a challenge for theory. This requires approaches beyond the widely employed framework provided by the density functional theory, wherein the Kohn-Sham ‘orbitals’ are treated as if they were real MOs, which is not the case. In this paper, we report results obtained by means of quantum chemical calculations, including the equation-of-motion coupled-cluster singles and doubles, which is the state-of-the-art of quantum chemistry for medium-size molecules like those considered here. These theoretical results are validated against data on the MO energy offset relative to the electrodes’ Fermi energy extracted from experiments for junctions based on 4,4’-bipyridine and 1,4-dicyanobenzene.